Razvojne značilnosti otrok v okviru forenzičnega razgovora - Pavšič Mrevlje, Tinkara (Psihološka obzorja (Ljubljana), 2013)
Children can be credible witnesses in court procedures given an adequately conducted forensic interview with them. This paper presents the most important features of a child's development (the cognitive and socioemotional developmentand the development of language and communication) and from these features derives the specific guidelines for forensic interviews of children. Due to the frequent belief that children can be led to false witnessing and that they do not differentiate between reality and fantasy the topics of lying and suggestibility are also discussed. At the end some practical suggestions are given with recommendations for trainings of all professionals working with children that are potential witnesses.
Keywords: forensic evaluation; forenzično ocenjevanje; forenzična psihologija; children; otroci; child; childhood development; razvoj otroka; witnesses; interview; intervju; memory; suggestibility; priče; spomin; sugestibilnost